Restoration of the facade of the church of San Pedro Apostol in Agost, Spain - Ivorra, Salvador; Spairani, Yolanda; Huesca, José Antonio; Saura, Pascual; Jordá, Enrique (Revista ALCONPAT, 2024)
This work describes the studies and the intervention carried out for the restoration of the facade of San Pedro Apostol in the parish church of Agost. This facade was made at the end of the 18th century in limestone. After an initial inspection and graphic survey of the facade, the lesions, their origin, and the solution to them were identified by using advanced restoration techniques. The stone elements damaged or destroyed by the passage of time are composed of calcite, dolomite and silica, with plaster joints, and have been reconstructed either through the use of new elements or, for the most part, through systems of recovery of the initial volume with the use of a light core of polystyrene, lime mortars, expanded clay, fiberglass and carbon together with infiltrations of resins in the disintegrated areas. After a delicated intervention process using innovative techniques, the facade was completed in June 2023.